NSC 18725, a Pyrazole Derivative Inhibits Growth of Intracellular Mycobacterium tuberculosis by Induction of Autophagy - Arora, Garima; Gagandeep,; Behura, Assirbad; Gosain, Tannu Priya; Shaliwal, Ravi P.; Kidwai, Saqib; Singh, Padam; Kandi, Shamseer Kulangara; Dhiman, Rohan; Rawat, Diwan S.; Singh, Ramandeep (Frontiers in Microbiology, 2020)
The increasing incident rates of drug-resistant tuberculosis (DR-TB) is a global health concern and has been further complicated by the emergence of extensive and total drug-resistant strains. Identification of new chemical entities which are compatible with first-line TB drugs, possess activity against DR- and metabolically less active bacteria is required to tackle this epidemic. Here, we have performed phenotypic screening of small molecule library against M. bovis BCG and identified 24 scaffolds that exhibited MIC99 values of at least 2.5 M. The most potent small molecule identified in our study was a nitroso containing pyrazole derivative, NSC 18725. We observed significant reduction in viable bacilli load of starved M. tuberculosis upon exposure to NSC 18725. The action of NSC 18725 was “synergistic” with isoniazid (INH) and “additive” with other drugs in our checkerboard assays. Structure-activity relationship (SAR) studies of the parent compound revealed that pyrazole derivatives without a functional group at fourth position lacked anti-mycobacterial activity in vitro. The derivative with para-chlorophenyl substitution at the first position of the pyrazole ring was the most active scaffold. We also demonstrate that NSC 18725 is able to induce autophagy in differentiated THP-1 macrophages. NSC 18725 also inhibited survival of both fast and slow growing mycobacteria inside human macrophages. Taken together, these observations support the identification of NSC 18725 as the lead molecule against M. tuberculosis, which synergizes with INH, is active against non-replicative mycobacteria and induces autophagy in macrophages.